The Concept of Bargaining for Punishment in Resolving Corruption Cases Drived by Technological Developments - Angga Aldilla Gussman; Usman Usman; Elly Sudarti; Sahuri Lasmadi; Herry Liyus (PT. Anagata Sembagi Education, 2024)
The development of information technology has provided new challenges in the fight against corruption, especially in terms of technology-based crimes that are difficult to detect. This research aims to analyze the application of the concept of bargaining for punishment in handling digital corruption cases and evaluate the challenges and benefits arising from its application. The method used in this research is a literature study and analysis of applicable legal concepts in the context of technology-based crimes. The results show that the application of this mechanism can accelerate the process of disclosing corruption cases involving technology, by offering incentives to reduce sentences to defendants who are willing to cooperate. However, the application of this concept also faces a number of challenges, such as the potential for abuse of the justice system, the complexity of obtaining valid evidence, and the need for regulatory updates and capacity building of law enforcement agencies. Overall, while bargaining for punishment offers great potential to accelerate the disclosure and recovery of state losses, its success relies heavily on the integrity of the legal system and strict oversight.